HISTOPATHOLGICAL CHANGES IN THE GILLS OF PUNTIUS TICTO (HAM) UNDER DIMETHOATE TOXICITY - GANESHWADE RAJU MARUTIRAO (The Bioscan, 2012)
Puntius ticto (Ham), freshwater fish exposed to lethal and two sublethal concentrations of dimethoate (5.012ppm, 2.506ppm and 1.253ppm) for 96hrs and 60 days respectively. Histopathological changes in the gills were observed after exposure period. Cells of gill lamellae i.e. epithelial, chloride cells, pillar cells shows clowdy swelling after acute toxicity; while marked degenerative changes i.e. curling andfusion of secondary gill lamellae, necrosis hypertrophic conditions observed during chronic exposure.